2020
DOI: 10.1021/acs.jpca.9b09127
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of New Belousov–Zhabotinsky Micro-Oscillators on the Basis of Silica Gel Beads

Abstract: We have fabricated and examined silica gel beads loaded with a catalyst of the Belousov−Zhabotinsky (BZ) reaction, tris(2,2′-bipyridyl)ruthenium(II) chloride, Ru(bpy) 3 Cl 2 , the BZ beads. The abilities of silica gel and the widely used ion-exchange resin (Dowex 50WX2) BZ beads to oscillate in a catalyst-free BZ solution are compared. The period of the BZ oscillations increases with an increase in the diameter (40−250 μm) of both types of the BZ beads. The ability of the ion-exchange resin beads to hold catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A number of reports on the information processing potential of networks composed of interacting chemical BZ-oscillators have appeared in the recent decade [33,34,35,36]. Our experiments have shown that networks of oscillators formed by touching droplets containing water solution of reagents of an oscillatory BZ-reaction can be stabilized by lipids dissolved in the surrounding oil phase.…”
Section: Introductionmentioning
confidence: 69%
“…A number of reports on the information processing potential of networks composed of interacting chemical BZ-oscillators have appeared in the recent decade [33,34,35,36]. Our experiments have shown that networks of oscillators formed by touching droplets containing water solution of reagents of an oscillatory BZ-reaction can be stabilized by lipids dissolved in the surrounding oil phase.…”
Section: Introductionmentioning
confidence: 69%
“…A high uniformity of droplets that form the network can be achieved if droplets are generated in a microfluidic device [ 32 ]. One can also use DOVEX beads or silica balls [ 33 ] to immobilize the catalyst and inhibit oscillations by illumination or electric potential [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bubbles of gas can appear between droplets, deform them, and change interactions between oscillators. We therefore believe that solid objects loaded with the catalyst, like DOWEX beads (Kuze et al, 2019 ) or silica gel beads (Mallphanov and Vanag, 2020 ), seem to be more suitable for experiments with information processing using a network of oscillators. Also, the strategy of optical communication described by Gentili et al ( 2017 ) can be applied to control interactions between oscillators and the inflow of input data.…”
Section: Discussionmentioning
confidence: 99%